2019
DOI: 10.1002/anie.201912552
|View full text |Cite
|
Sign up to set email alerts
|

Rational Synthesis of Amorphous Iron‐Nickel Phosphonates for Highly Efficient Photocatalytic Water Oxidation with Almost 100 % Yield

Abstract: A simple solvent ligation effect was successfully used to disrupt the growth of a model compound, Fe[(OH)(O3P(CH2)2CO2H)]⋅H2O (MIL‐37), into an extended 2D structure by replacing water with dimethylformamide (DMF) as the solvent during the synthesis. Owing to the lack of −OH group, which provides the corner‐sharing (binding) oxygen atoms for the octahedra, an amorphous and porous structure is formed. When Fe3+ is partially replaced by Ni2+, the amorphous structure remains and the resultant binary metal catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 58 publications
(18 reference statements)
1
12
0
Order By: Relevance
“…Previous studies showed that the TMC with an amorphous structure could deliver superior OER performance than the crystalline counterparts. , The advantage of the amorphous structure is that the long-range disordered metallic atoms and unsaturated coordination bonds can benefit the microstructural and compositional reconstruction of the precatalysts into highly active metal oxy­(hydroxide) motifs during the OER process, such as the amorphous NiFeMo oxides and trimetallic phosphate could undergo rapid surface self-reconstruction to oxygen vacancy-rich Ni–Fe oxy­(hydroxide) layers. However, most of the reported precatalysts can only undergo shallow surface reconstruction, limiting the utilization of the inner active components.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the TMC with an amorphous structure could deliver superior OER performance than the crystalline counterparts. , The advantage of the amorphous structure is that the long-range disordered metallic atoms and unsaturated coordination bonds can benefit the microstructural and compositional reconstruction of the precatalysts into highly active metal oxy­(hydroxide) motifs during the OER process, such as the amorphous NiFeMo oxides and trimetallic phosphate could undergo rapid surface self-reconstruction to oxygen vacancy-rich Ni–Fe oxy­(hydroxide) layers. However, most of the reported precatalysts can only undergo shallow surface reconstruction, limiting the utilization of the inner active components.…”
Section: Introductionmentioning
confidence: 99%
“…vacancy since DMF has a stronger solvation effect on Fe 3? than Ni 2? [15]. It has been reported the existence of Ni 3? in the structure of the catalyst is more conducive to the OER activity as it could be used as the main redox site to decrease the overpotential for water oxidation reaction [25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…Studies revealed that the distorted metal coordination structure with a longer bond length of Co-O and Co-Co bond of cobalt diphosphate made important contributions to the high OER activity. In our recent work, an amorphous iron-nickel phosphonate was synthesized by a simple solvent ligation effect [15]. Owing to replace water with dimethylformamide and lack of -OH group, the amorphous and porous structure is constructed, which exerting highly active for photocatalytic OER.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous catalysis plays a vital role in chemical transformations (e.g., energy related fields, asymmetric catalysis, and pharmaceutical synthesis), [119][120][121] where the development of low-cost and high-efficient catalysts has been considered to be the key to breaking performance bottlenecks. [122][123][124] The design of homogeneous catalysts not only needs to consider how to improve the activity and selectivity, but also needs to solve the difficulty of catalyst/product separation due to the same phase of catalysts with the reactants in a heterogeneous reaction.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…These impressive properties make porous metal phosphonates promising as ideal carriers for heterogeneous catalysts. In this section, we reviewed the applications of porous metal phosphonates in heterogeneous catalysis, [119][120][121][122][123][124][125][126][127][128] which are specifically discussed based on metal sites, phosphonate functional groups, and their derivatives. A summary of the representative examples of catalytic porous metal phosphonates is presented in Table 5.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%